Continuous graphene and carbon nanotube based high flexible and transparent pressure sensor arrays. (25th February 2015) - Zhang, Xiaoxiang; Hu, Songtao; Wang, Meng; Yu, Jia; Khan, Qasim; Shang, Jintang; Ba, Long
Abstract: The transparent pressure sensing arrays durable to severe deformation are fabricated by covering the continuous graphene sheets on the tip of thermal plastic polyurethane (TPU) pyramids, while most of the TPU surface is covered by a layer of densely entangled single wall carbon nanotubes. The transparency of the conducting layer exceeds 91%. The capacitance variations between TPU surface and flat electrode under compressive deformation show high sensitivity and a broad dynamic range from hundreds Pa to MPa. The measured capacitance variations show high load sensitivity and stability under repeated deformation cycles. Finite element numerical simulations present that the contact area change under deformation increases the capacitance variation. The high stability of the capacitance response to fluctuated loads demonstrates that graphene layer on the surface of TPU pyramids maintains the continuity of electric contact under a large deformation ratio and high repeating cycles. 16 × 16 arrays are connected to a circuit and a typical load distribution is regenerated by mapping the local capacitance variations on the arrays with sub-minimeter spatial resolution.